Fungal inoculants in the field: Is the reward greater than the risk?. (29th September 2017) - Hart, Miranda M.; Antunes, Pedro M.; Chaudhary, Veer Bala; Abbott, Lynette K.
Abstract: Biofertilizers are a large part of the global agricultural economy. Recently, there has been an increase in the number of companies producing fungal inoculants. Whether these inoculants are useful is not clear; they are difficult to monitor in the field. The unintended consequences of inoculants in natural systems is not known, but if invasive, they may pose a threat to soil and plant biodiversity and ecosystem functioning. A plain language summary is available for this article. Abstract : Plain Language Summary